2019
DOI: 10.3917/espri.1911.0097
|View full text |Cite
|
Sign up to set email alerts
|

Ceux qui restent

Abstract: Un sociologue plonge dans le quotidien de ceux qui restent dans les campagnes en déclin, faute de disposer des ressources pour être mobiles. Il témoigne de la persistance de consciences collectives, qui conduit au mouvement des Gilets jaunes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…In the case of the Yellow Vests, people participated intuitu personae. Some researchers have hypothesized that participation was nonetheless invisibly structured by the informal networks which effectively organize life in the French countryside (Charmes, 2011;Coquard, 2019). But our research showed that most participants did not know each other before the mobilization.…”
Section: Intergenerational Downgrading As a Trigger For Popular Angercontrasting
confidence: 61%
See 2 more Smart Citations
“…In the case of the Yellow Vests, people participated intuitu personae. Some researchers have hypothesized that participation was nonetheless invisibly structured by the informal networks which effectively organize life in the French countryside (Charmes, 2011;Coquard, 2019). But our research showed that most participants did not know each other before the mobilization.…”
Section: Intergenerational Downgrading As a Trigger For Popular Angercontrasting
confidence: 61%
“…Some Antoine Bernard de Raymond, Sylvain Bordiec, « Bridging the gap in social movement research: family as a vehicle for mobilization for the Yellow Vests », French Politics, 2022 Version pré-publication, ne pas citer 8 researchers have hypothesized that the informal networks of friendships that structure rural spaces, which function as invisible clubs conditioning access to different opportunities (jobs, romantic encounters, etc.) played a key part in the movement (Coquard, 2019). Nevertheless, when Yellow Vests were asked about their pre-movement acquaintances, they most often stated that they did not know the other participants, or very few of them.…”
Section: Family In Social Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guilluy, et plus récemment de David Goodhart [2019] qui oppose les « somewheres » -populaires, modestes, ancrés dans un territoire rural ou anciennement industriel, perdants de la mondialisation et favorables au Brexit -aux « anywheres » -cultivés, plus aisés, urbains et partisans du « Remain ». Les gilets jaunes peuvent évoquer cette opposition et ont donné lieu à des discussions un peu vaines concernant leur orientation électorale, mais ils invitent surtout à mieux connaître les modes de vie dans ces territoires et milieux sociaux, comme le proposent de récentes publications sociologiques [Coquard, 2019] ou littéraires [Mathieu, 2018], ayant toutefois laissé un peu de côté les budgets de famille [Coutard, Dupuy et Fol, 2002]. Il se pourrait que se joue là une partie du destin politique et social français, ce qui invite les sciences sociales à investir de nouveau ces thématiques.…”
Section: La Centralité De L'automobile Dans L'économie Domestique Des...unclassified